Matching emerging formic acid synthesis processes with application requirements. Issue 6 (2nd March 2022) - Thijs, Barbara; Rongé, Jan; Martens, Johan A.
Abstract : Electrolytic formic acid synthesis delivers green formic acid at the right concentration for emerging applications. Abstract : Formic acid is gaining interest as a carbon capture and utilization (CCU) product produced electrochemically from CO2, water and renewable energy. A common premiss is that concentrated formic acid is the desired product. This originates from the current situation with centralized large-scale industrial production of a concentrated product for reasons of economizing on distribution costs. This premiss is shaping research on green formic acid synthesis, attempting to eliminate water as much as possible from the electrolysis product. Water elimination adds substantially to the overall production cost. Interestingly, the application field of formic acid is shifting to more diluted feedstock. Emerging applications can handle diluted formic acid, and even require dilution. Examples are the use of formic acid as an energy vector, hydrogen gas carrier, syngas storage medium and carbon source for bioprocesses. This review provides an overview of formic acid concentration requirements in emerging applications. The matching of the product specifications from the electrochemical formic acid production process with the requirements of emerging applications is documented.